2015
DOI: 10.3233/jpd-140524
|View full text |Cite
|
Sign up to set email alerts
|

Concerns About Falling in Parkinson’s Disease: Associations with Disabilities and Personal and Environmental Factors

Abstract: Abstract.Background: Fear of falling can be conceptualized in different ways, e.g., as concerns about falling or low fall-related selfefficacy. It is common in people with Parkinson's disease (PD), and there is growing knowledge about its contributing factors. However, previous multivariate studies have mainly focused on fear of falling in relation to PD-related disabilities, and less is known about the associations between fear of falling and personal and environmental factors. Objective: To identify explanat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
42
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 37 publications
(54 citation statements)
references
References 45 publications
9
42
3
Order By: Relevance
“…Based on data from the larger project [26] that this study is part of, general selfefficacy has been shown to independently contribute to life satisfaction [ 43], but not to concerns about falling [44] in people with PD. Other PD-studies have reported that selfefficacy is of importance for engagement in exercise [45] and self-management [46].…”
Section: Discussionmentioning
confidence: 98%
“…Based on data from the larger project [26] that this study is part of, general selfefficacy has been shown to independently contribute to life satisfaction [ 43], but not to concerns about falling [44] in people with PD. Other PD-studies have reported that selfefficacy is of importance for engagement in exercise [45] and self-management [46].…”
Section: Discussionmentioning
confidence: 98%
“…As this is the first study to use multivariable analyses to investigate determinants of FOF in persons with late effects of polio, our results are difficult to compare with others. However, in persons with other neurologic diseases, such as stroke and Parkinson disease, decreased balance [33], muscle weakness in the lower limbs [27], and walking limitations [24,34] have been shown to be associated with FOF.…”
Section: Discussionmentioning
confidence: 99%
“…The score for each item is summarized, yielding a total score of 16‐64 points; a greater score indicates that the person is more concerned about falling. The FES‐I score also can be categorized as low FOF (16‐19 points), moderate FOF (20‐27 points), or high FOF (28‐64 points) [23,24]. The FES‐I has shown good psychometric properties [25] and is used commonly in persons with different neurologic and neuromuscular diseases [10,14,15,24,26,27].…”
Section: Methodsmentioning
confidence: 99%
“…In order to be able to design efficient interventions for FOF in people with PD, it is important to gain an increased understanding of predictive factors of FOF. Seven previous cross-sectional studies used multivariable analyses in order to identify factors associated with FOF in people with PD [8,10,[19][20][21][22][23]. Four out of the seven studies addressed fallrelated self-efficacy [8,10,20,21].…”
Section: Introductionmentioning
confidence: 99%